O conceito de gene em discursos de professores-pesquisadores : evolução em andamento ou revolução permanente? - Ramos, Fernanda Peres (2010)
During the historical course of science several perspectives were evident in its construction. This construction was established in a peculiar way among the distinct historical contexts and scientific communities of each time, based by different methods, that in their turn received a large part of their influence from several philosophical conception that has been formed in the pass of history of science. Among the chains of greatest influence in scientific construction until the XXI century there is the positivism, characterized by the idea of progressive and cumulative science. Such philosophical conception are confronted by the ideas that characterizes the contemporary Science Paradigm, based on the uncertain and unforeseen of science. However, in the field bimolecular genetics, the unleashed researches in the end of century XX generated great expectations to general public, mainly for curing genetics diseases, contributing to reinforce, in social imaginary a Salvationist science ruled of paper in commutative linearity of knowledge, characterized as Paradigm of Modern Science. The epistemological periods about construction of science and the knowledge about the gene are the themes of this study that has as goal to analyze the research-teacher discourses as goal identify the trends expressed with relation in the science as a way of production of knowledge e their conceptions about the conception of gene. The methodological choice for Discoursing Analyze was the Phenomenology, such proved relevant to this research, since has as focus the several ways of manifestation in discourses, present many time not only in speech, but in the silence and on ideology implicitly expressed. The fenomenoloficas analyze showed the presence of a conception pattern of linear and cumulative science, as well, discursive manifestations immersed in transience, showing a transitory pattern between the values based on cumulative linearity and a complexity multicausal science, own of modern and contemporary science. The strong presence of modern science values in scientific discourses, reveal as traces of discourses based in values of multicausal complexity of science are as the evidences critical manifestation to a paradigm still dominant in our society.